AMIR TEMUR AND THE PERIOD OF THE TEMURIDS - Teshaboyeva Nafisa Zubaydulla qizi; Xalilova Sevinch (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation:this passage explores the historical significance of Amir Temur and the Timurid period and their role in shaping political, cultural, and international relations in Central Asia. It highlights Amir Temur’s leadership, his efforts to unite vast territories, and his contribution to establishing a powerful and centralized state. The article emphasizes the importance of major Timurid cities such as Samarkand, Herat, Bukhara, and Shahrisabz, which became centers of science, culture, architecture, and diplomacy.The passage also explains how Amir Temur used diplomacy, trade relations, and strategic alliances to strengthen international connections with Europe, the Middle East, and Asia. It discusses the cultural and scientific achievements of the Timurid period, particularly in architecture, astronomy, literature, and education, which enhanced the region’s global prestige.Furthermore, the article examines the political and economic impact of the Timurid state, including the development of trade routes, state administration, and military organization. Despite internal conflicts after Amir Temur’s death, the passage concludes that the Timurid period left a lasting legacy and continues to play a significant role in understanding Uzbekistan’s historical identity and its contribution to world civilization.